2019
DOI: 10.1111/eje.12437
|View full text |Cite
|
Sign up to set email alerts
|

Next generation of dentists moving to amalgam‐free dentistry: Survey of posterior restorations teaching in North America

Abstract: Objectives:The dental field is gradually reducing the use of amalgam and moving towards adhesive restoration. This change is in accordance with the advancement and improvement of composite resin materials and adhesion systems. Consequently, posterior cavity preparations teaching should be re-examined to determine whether dental schools are adapting their curriculum to fit the current trends in dentistry and what rationale supports their decisions.Methods: An online questionnaire was constructed to assess the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…This concurred with the study conducted in Israel, which found that today some universities teach composite resin before introducing amalgam. 26 This study's results indicated that dental amalgam is now less than 50% of the total practical time. Similar results were seen in the United Kingdom, where the researchers found that preclinical time for resin composite has increased since 1997.…”
Section: Compressive Strength Of Amalgammentioning
confidence: 85%
See 1 more Smart Citation
“…This concurred with the study conducted in Israel, which found that today some universities teach composite resin before introducing amalgam. 26 This study's results indicated that dental amalgam is now less than 50% of the total practical time. Similar results were seen in the United Kingdom, where the researchers found that preclinical time for resin composite has increased since 1997.…”
Section: Compressive Strength Of Amalgammentioning
confidence: 85%
“…An Israeli study had similar results, where the researchers found that, in complex restorations, amalgam was still the material of choice. 26 The majority of the third-year students were aware of the Minamata Convention and its implications, including the phase-down of dental amalgam. Most of the secondyear students had not heard of the Minamata Convention, and just 18% (n= 7) were aware of the phase-down of dental amalgam.…”
Section: Compressive Strength Of Amalgammentioning
confidence: 99%
“…33 Another problem to consider is the lack of clear guidelines in some countries for tooth preparation for resin composite restorations teaching. 34 This study shows for the first time how steady the decline of the use of amalgam restorations is in a dental school in Australia, using the average annual percentages change (AAPC) method. This method allows the use of a single number to describe the average annual percentage changes (AAPCs) over multiple years.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent mechanical and aesthetic properties of DRCs help them meet the demands of daily chewing and aesthetic appearance in terms of tooth color [ 2 , 3 ]. In addition, with corresponding adhesive systems, the composites bond to tooth tissues without the need for extensive preparation of the dental cavity, avoiding the need for excessive removal of healthy dental tissues, which is common in the case of dental amalgam [ 4 , 5 ]. Thus, DRCs have attracted great interest in both scientific research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%